The important role of in-situ simulation in preparing surgeons for the COVID-19 pandemic. Issue 5 (October 2021) - Montauban, Pierre; Balakumar, Charannya; Rait, Jaideep; Zarsadias, Prizzi; Iqbal, Sara; Aravind, Biju; Shrestha, Ashish; Fernandes, Roland; Shah, Ankur; ,; Basnyat, Pradeep; Harinath, Gandrasupalli; et al.
Abstract: Background: Effective training is vital when facing viral outbreaks such as the SARS Coronavirus 2 (SARS-CoV-2) outbreak of 2019. The objective of this study was to measure the impact of in-situ simulation on the confidence of the surgical teams of two hospitals in assessing and managing acutely unwell surgical patients who are high-risk or confirmed to have COVID-19. Methods: This was a quasi-experimental study with a pretest-posttest design. The surgical teams at each hospital participated in multi-disciplinary simulation sessions to explore the assessment and management of a patient requiring emergency surgery who is high risk for COVID-19. The participants were surveyed before and after receiving simulation training to determine their level of confidence on a Visual Analog Scale (VAS) for the premise stated in each of the nine questions in the survey, which represented multiple aspects of the care of these patients. Results: 27 participants responded the pre-simulation survey and 24 the one post-simulation. The level of confidence (VAS score) were statistically significantly higher for all nine questions after the simulation. Specific themes were identified for further training and changes in policy. Conclusion: In-situ simulation is an effective training method. Its versatility allows it to be set up quickly as rapid-response training in the face of an imminent threat. In this study, it improved the preparedness of two surgical teams for the challenges of the COVID-19 pandemic. Highlights: Simulation was used to prepare surgeons for challenges of the COVID-19 pandemic. Level of confidence improved significantly as a result of the simulation training. It was a key strategy to test and improve the Standard Operating Procedures.